Inhibition of Extracellular Calcium Influx Results in Enhanced IL-12 Production in LPS-Treated Murine Macrophages by Downregulation of the CaMKKβ-AMPK-SIRT1 Signaling Pathway. (30th May 2016) - Liu, Xin; Wang, Ning; Zhu, Yuanfeng; Yang, Yongjun; Chen, Xiaoli; Fan, Shijun; Chen, Qian; Zhou, Hong; Zheng, Jiang
Abstract : Activated macrophages are the primary sources of IL-12, a key cytokine bridging innate and adaptive immunity. However, macrophages produce low amounts of IL-12 upon stimulation and the underlying regulatory mechanism remains unclear. In this study, we found a new calcium-dependent mechanism that controlled IL-12 production in LPS-treated murine macrophages. First, LPS was demonstrated to induce extracellular calcium entry in murine peritoneal macrophages and inhibition of calcium influx resulted in marked enhancement in IL-12 production. Then, withdrawal of extracellular calcium was found to suppress CaMKKβ and AMPK activation triggered by LPS while chemical inhibition or genetic knockdown of these two kinases augmented LPS induced IL-12 production. AMPK activation increased the NAD + /NADH ratio and activated Sirtuin 1 (SIRT1), a NAD + -dependent deacetylating enzyme and negative regulator of inflammation. Chemical inhibitor or siRNA of SIRT1 enhanced IL-12 release while its agonist suppressed IL-12 production. Finally, it was found that SIRT1 selectively affected the transcriptional activity of NF- κ B which thereby inhibited IL-12 production. Overall, our study demonstrates a new role of transmembrane calcium mobilization in immunity modulation such that inhibition of calcium influx leads to impaired activation of CaMKK β -AMPK-SIRT1 signaling pathway which lifts restriction on NF- κ B activation and results in enhanced IL-12 production.